A risk-benefit analysis of maintaining an aerobic-endurance triathlon training program during pregnancy: A review - Holt, E. L.; Holden, A. V. (Science & Sports, 2018)
Objectives: Possible risks and benefits of an endurance-based triathlon training program during pregnancy were assessed. News: Vigorous exercise throughout the third trimester can lower birth weight by 400g, but other indices of fetal well-being are unaffected. Fetal heart rate increases during exercise, remaining within the normal range (120-160 beats min-1). Swimming, cycling and running do not affect fetal morbidity or mortality. Performance indices such as aerobic capacity can be maintained through continuation of training. Prospects and projects: Will aid the counselling of women during pregnancy. To date, no research exists regarding triathlon training during pregnancy, future studies could investigate multi-sport training whilst pregnant. Conclusion: Pregnancy does not require complete cessation of triathlon training and can include each of the three sports. However, maternal heart rate (MHR) should not exceed 90% of maximal.